Dynamic Mechanical Analysis and Creep-recovery behaviour of Polyvinyl Alcohol based cross-linked Biocomposite reinforced with Basalt fiber. (20th September 2019) - Jain, Naman; Verma, Akarsh; Singh, V K
Abstract: Polyvinyl alcohol (PVA) is a synthetic, semi-crystalline, biodegradable and water soluble polymer having moderate mechanical properties. In the present investigation, restriction in water absorption of PVA is achieved by cross-linking with hydrochloric acid (HCl) which is confirmed by Fourier transform infrared spectroscopy (FTIR) and water uptake test. Results suggest that due to the formation of cross-linked bonds thermal and mechanical properties of PVA based cross-linked composite are improved as compared to pristine PVA. Further improvement in physical, mechanical and thermal properties is achieved by reinforcing basalt fibers. Tensile test results show that ultimate tensile strength (UTS) of basalt fiber reinforced composites increased by 79.4% as compared to the cross-linked PVA. Dynamic mechanical analysis of fabricated composites has been carried out to determine the storage modulus, glass transition temperature and activation energy. Effect of stress and temperature on creep and recovery behavior of cross-linked PVA and basalt fiber reinforced composite are studied and burger model is used to study the creep data.